Error Analysis and Global Superconvergences for the Signorini Problem with Lagrange Multiplier Methods (Journal of Computational Mathematics, 2002)
In this paper, the finite element approximation of the Signorini problem is studied by using Lagrange multiplier methods with piecewise constant elements. Optimal error bounds are obtained and iterative algorithm and its convergence are given. Furthermore, global superconvergences are proved.